The role of propranolol in the treatment of infantile haemangioma - Moodley, Sean Thirumalay (Division of Plastic and Reconstructive Surgery, 2015)
There has been a change in the management of infantile haemangioma with the introduction of propranolol. The aim of this study is to retrospectively evaluate a simple treatment for infantile haemangioma at the Red Cross War Memorial Children’s Hospital (RCWMCH) and document the results. While it is known that all haemangiomas undergo involution at some stage, some haemangiomas pose certain problems. These relate mainly to visual axis obstruction and aesthetics. Subjects are children in the first two years of life presenting with haemangiomas. All patients were treated with oral propranolol in conjunction with haemangioma size documentation, using a simple radiological modality, i.e. ultrasound imaging. Patients are followed up and clinical and radiological evaluations are undertaken to observe changes in size and appearance. Propranolol is non-selective β-adrenergic antagonist that is used extensively for the treatment of a multitude of disorders, mainly cardiovascular indications. The main adverse effects include bradycardia, hypotension and bronchospasms. For the purposes of this study, all subjects were routinely examined, especially with regard to the cardiopulmonary systems. Any perceived anomaly was referred to the cardiorespiratory physicians at RCWMCH for further evaluation, which includes all the necessary investigations such as electrocardiograms(ECG) and echocardiograms. Therefore, only fit healthy patients were selected for this study. Patients are educated and fully informed regarding the adverse effect profile of propranolol, and advised of the appropriate route of management.